2014
DOI: 10.1038/jcbfm.2014.105
|View full text |Cite
|
Sign up to set email alerts
|

Dual Vulnerability of TDP-43 to Calpain and Caspase-3 Proteolysis after Neurotoxic Conditions and Traumatic Brain Injury

Abstract: Transactivation response DNA-binding protein 43 (TDP-43) proteinopathy has recently been reported in chronic traumatic encephalopathy, a neurodegenerative condition linked to prior history of traumatic brain injury (TBI). While TDP-43 appears to be vulnerable to proteolytic modifications under neurodegenerative conditions, the mechanism underlying the contribution of TDP-43 to the pathogenesis of TBI remains unknown. In this study, we first mapped out the calpain or caspase-3 TDP-43 fragmentation patterns by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 41 publications
1
64
0
Order By: Relevance
“…TBI is a major risk factor for developing dementia, and increased levels of soluble amyloid b peptide and deposition of amyloid plaques explain the occurrence of dementia (Rosso et al, 2003;Loane et al, 2009;DeKosky et al, 2010;Querfurth and LaFerla, 2010;Rossor et al, 2010;Tran et al, 2011;Wang et al, 2012a,b). However, the amyloid hypothesis cannot explain why TDP-43 proteolysis occurs in patients with a single episode of TBI and chronic traumatic encephalopathy (McKee et al, 2010;Yang et al, 2014). Furthermore, TDP-43 inclusions are considered as neuropathological hallmarks of FTD (Seelaar et al, 2011;Sieben et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…TBI is a major risk factor for developing dementia, and increased levels of soluble amyloid b peptide and deposition of amyloid plaques explain the occurrence of dementia (Rosso et al, 2003;Loane et al, 2009;DeKosky et al, 2010;Querfurth and LaFerla, 2010;Rossor et al, 2010;Tran et al, 2011;Wang et al, 2012a,b). However, the amyloid hypothesis cannot explain why TDP-43 proteolysis occurs in patients with a single episode of TBI and chronic traumatic encephalopathy (McKee et al, 2010;Yang et al, 2014). Furthermore, TDP-43 inclusions are considered as neuropathological hallmarks of FTD (Seelaar et al, 2011;Sieben et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Unfortunately, motor neuron diseases often exhibit ubiquitin-and TDP-43-immunoreactive inclusion bodies, making it difficult to determine whether TDP-43 proteinopathy is caused by head injury. Yang et al showed that protease-generated TDP-43 fragments may gain neurotoxic function and induce secondary injury, and that TDP-43 and its fragments may have biomarker utilities in TBI patients (Yang et al, 2014). However, in another study by Johnson et al that aggregates of TDP-43 were not increased acutely or long-term following TBI (Johnson et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…26,39 While the number of plasma samples is still relatively small within the cohort, the TRACK-TBI pilot dataset was selected for this study because it is well-characterized with 13 published articles regarding various components of these TBI patients across the full range of TBI severity-including proteomic and genetic biomarkers, neuroimaging, and outcome data. 31,36,37,[40][41][42][43] Based on the 217 subjects with available biosamples from this cohort, we identified that anti-GFAP autoantibody levels were elevated in acute plasma samples from brain injury subjects who had a self-reported history of previous TBI with or without LOC when compared with patients with acute TBI without self-reported previous TBI (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that various deletion mutations of TDP-43 lost its ability to suppress the expression of tau. Thus, cleavage of TDP-43 due to activation of calpain (67,75) and AEP (68) caused by traumatic brain injury may contribute to tau pathology in CTE.…”
Section: Discussionmentioning
confidence: 99%